COMPREHENSIVE REVIEW OF PUBLIC HEALTH CAMPAIGNS, MEDIA INFLUENCE, AND HEALTH EDUCATION - KHURIDAH, BATOOL ALI MOHAMMAD; ALSAMEEN, EMAN HASSAN; ALSADIQ, ABBAS MOHAMMED; ALQAHTANI, ABDULLAH AHMAD; AL-OSAIF, ‏ AFRAH ABDULAZIZ; AL SHIBAN, BANDAR ABDULLAH HUSSIN; AL RIZQ, MOHAMMAD NASSER; ALABID, WESSAM HASSAN; ALHAFFEH, IBRAHIM AHMED; ALOSAIF, QASIM ABDRABALRASOOL JASIM (Journal of Ecohumanism, 2024)
This paper explores public health interventions, media bias, and health information dissemination on the overall population health. It becomes clear that public health campaigns have played a significant role in explaining, decreasing, and changing health disparities, disease incidence, and behaviors at the individual and community levels. The review seeks to examine approaches used in public health campaigns and, eventually, the media influences public health communication and the place health education has in modifying the populace’s health. These results provide information on the barriers and outcomes of these programs, which could help optimize further interventions.